2018
DOI: 10.1186/s13048-018-0466-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of Ficus deltoidea against BPA-induced impairments of the follicular development, estrous cycle, gonadotropin and sex steroid hormones level of prepubertal rats

Abstract: Ficus deltoidea is one of the well-known medicinal plants in Malaysia that is traditionally used by the Malay community to treat various ailments and for maintenance of female reproductive health. The objective of this study is to evaluate the potential protective roles of Ficus deltoidea against BPA-induced toxicity of the pituitary-ovarian axis in pre-pubertal female rats. In this study, four groups of pre-pubertal female Sprague Dawley rats were administered with the followings by oral gavage for a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Furthermore, in rat female pups postnatally exposed, from PND1 to PND10, to subcutaneous administration of high BPA doses decreased GnRH-induced serum LH release at PND13 and in adulthood during estrus; this effect was not found at low BPA doses [79]. Conversely, several studies reported that prenatal and postnatal exposure to low BPA doses reduced serum LH and FSH levels [88] or that exposure to low BPA doses with different administration routes did not affect either circulating LH [29,81,87,89] or FSH [29-31, 79, 87, 89] levels in female adult mice and rats observed in different phases of estrus cycle. Finally, an up-regulation of FSH, but not LH, messenger expression has been observed in mouse female offspring perinatally exposed by gavage administration to low BPA doses [29].…”
Section: Pituitarymentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, in rat female pups postnatally exposed, from PND1 to PND10, to subcutaneous administration of high BPA doses decreased GnRH-induced serum LH release at PND13 and in adulthood during estrus; this effect was not found at low BPA doses [79]. Conversely, several studies reported that prenatal and postnatal exposure to low BPA doses reduced serum LH and FSH levels [88] or that exposure to low BPA doses with different administration routes did not affect either circulating LH [29,81,87,89] or FSH [29-31, 79, 87, 89] levels in female adult mice and rats observed in different phases of estrus cycle. Finally, an up-regulation of FSH, but not LH, messenger expression has been observed in mouse female offspring perinatally exposed by gavage administration to low BPA doses [29].…”
Section: Pituitarymentioning
confidence: 93%
“…Increased E2 circulating levels have been also reported in adult mice after acute low BPA administration [78]. Conversely, in further studies conducted on female adult mice and rats treated with low BPA doses by oral and gavage administration, no changes in circulating E2 levels have been reported during proestrus and diestrus [87,88]. Moreover, in female adult rats exposed in adulthood to low BPA doses by gavage administration decreased circulating E2 levels have been found during estrus [30]; the decrease in circulating E2 levels in female adult rats exposed to low BPA doses have been associated to a down-regulation of StAR and aromatase protein synthesis, as confirmed by immunohistochemical studies on ovary [30].…”
Section: Ovarymentioning
confidence: 98%
See 2 more Smart Citations
“…Epidemiological studies also report that BPA has a toxic effect on male and female reproductive organs at the environmentally relevant level of exposure 38 . Even at a low dose of BPA, it is supposed to disturb the semen production in men and oocyte production in women by the interrupting the synthesis of sex steroids 96 . But the effects of BPA on reproductive hormones and semen quality in different epidemiologic studies are inconsistent 97 .…”
Section: Bpa Induced Oxidative Stress and Generation Of Rosmentioning
confidence: 99%